A Roman Egyptian Painting Workshop: Technical Investigation of the Portraits from Tebtunis, Egypt. (24th November 2017) - Salvant, J.; Williams, J.; Ganio, M.; Casadio, F.; Daher, C.; Sutherland, K.; Monico, L.; Vanmeert, F.; De Meyer, S.; Janssens, K.; Cartwright, C.; Walton, M.
Abstract : Roman‐period mummy portraits are considered to be ancient antecedents of modern portraiture. However, the techniques and materials used in their manufacture are not thoroughly understood. Analytical study of the pigments as well as the binding materials helps to address questions on what aspects of the painting practices originate from Pharaonic and/or Graeco‐Roman traditions, and can aid in determining the provenance of the raw materials from potential locations across the ancient Mediterranean and European worlds. Here, one of the largest assemblages of mummy portraits to remain intact since their excavation from the site of Tebtunis in Egypt was examined using multiple analytical techniques to address how they were made. The archaeological evidence suggests that these portraits were products of a single workshop and, correspondingly, they are found to be made using similar techniques and materials: wax‐based and lead white–rich paint combined with a variety of iron‐based pigments (including hematite, goethite and jarosite), as well as Egyptian blue, minium, indigo and madder lake to create subtle variations and tones.